Negative DNA supercoiling makes protein-mediated looping deterministic and ergodic within the bacterial doubling time. Issue 20 (1st November 2021) - Yan, Yan; Xu, Wenxuan; Kumar, Sandip; Zhang, Alexander; Leng, Fenfei; Dunlap, David; Finzi, Laura
Abstract: Protein-mediated DNA looping is fundamental to gene regulation and such loops occur stochastically in purified systems. Additional proteins increase the probability of looping, but these probabilities maintain a broad distribution. For example, the probability of lac repressor-mediated looping in individual molecules ranged 0–100%, and individual molecules exhibited representative behavior only in observations lasting an hour or more. Titrating with HU protein progressively compacted the DNA without narrowing the 0–100% distribution. Increased negative supercoiling produced an ensemble of molecules in which all individual molecules more closely resembled the average. Furthermore, in only 12 min of observation, well within the doubling time of the bacterium, most molecules exhibited the looping probability of the ensemble. DNA supercoiling, an inherent feature of all genomes, appears to impose time-constrained, emergent behavior on otherwise random molecular activity.